Analisis Partisipasi dan Pemberdayaan Perempuan dalam Pelaksanaan Pembangunan Kampung Tematik: Studi Kasus Kampung Tematik Seni Jurang Belimbing Kota Semarang - Widiyawati Setia Cahyaningrum; Laila Kholid Alfirdaus (Journal of Politic and Government Studies, 2026)
This study analyzes the participation and empowerment of women in the development of the Jurang Belimbing Art Thematic Village, Semarang City, based on the Semarang Mayor Regulation Policy Number 22 of 2018. The research background is based on gender inequality that is still prominent in community development. Women are often marginalized despite playing a vital role in the preservation of traditional art culture. This study highlights the importance of women's involvement as agents of change to achieve inclusive and sustainable development, considering that national and regional data show the significant contribution of women in the arts and culture sector. The research uses a gender perspective as a social construct, women's empowerment, and a ladder of community participation. The research method is qualitative with a case study approach, using data collection techniques through observation, in-depth interviews with informants, and analysis of policy documents and activity reports. The findings show women's participation is high at the operational level, but low at strategic planning, placing it at the level of tokenism. Empowerment programs such as arts and crafts training are incidental, with no ongoing support. The main challenges include patriarchal norms, the double burden of women, limited institutional resources, and the lack of regeneration of the younger generation. The conclusion states that the top-down policy of Guardian Regulation No. 22/2018 has not integrated gender mainstreaming, thereby reproducing inequality. This research offers novelty through critical gender critique on art-based local development, recommending structural reforms for women's substantive empowerment.